Silent killer - a case report - Mohd Mussadik, Umul Khairil Fatimah; Hasim, Husna Syaza; Zaki, Hafizatul Solehah; Chng, Kay Ly (Academy of Medicine Malaysia, 2024)
ntroduction: This case report discusses the challenging situation forensic pathologists face when dealing with sudden unexpected death in a healthy young adult. While thyroid diseases rarely result in death, they can be a potential cause in some cases. The report highlights the importance of considering thyroid pathology as a possible factor in cases where all other potential causes have been ruled out. Case: A young adult male from Bangladesh was found unconscious in bed. No external injuries were observed, but the thyroid was obscured due to a cricothyroidotomy performed during resuscitation. Gross examination of other organs, including the heart, appeared normal. However, histological analysis revealed lymphocytic infiltration with significant destruction of follicles in the thyroid, as well as fibrotic changes in the SA node. Unfortunately, thyroid function tests were not conducted initially. While the exact cause of death remained unascertained, the possibility of lymphocytic thyroiditis as a contributing factor was considered. Discussion: Lymphocytic thyroiditis should be considered as a potential differential diagnosis for sudden unexpected death. Microscopic evaluation of the thyroid is often overlooked if gross findings are unremarkable and the patient’s history does not suggest thyroid disease. Therefore, routine microscopic examination of the thyroid is advised in cases of sudden death, as many cases present without significant clinical symptoms and normal gross findings. Ultimately, it is important to establish guideline for performing standard autopsies, particularly in cases of sudden unexpected death in young adults. It can help ensure thorough investigations and consideration of potential causes, including thyroid pathology.